Circular RNA circ_0008365 regulates SOX9 by targeting miR-338-3p to inhibit IL-1β-induced chondrocyte apoptosis and extracellular matrix degradation - Shengbin Shuai; Qianqian Cai; Yunxia Ou (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Background Osteoarthritis (OA) is a chronic disease that involves chondrocyte injury and dysfunction. CircRNAs participate in OA progression, but the roles of circRNAs in the occurrence of OA are unclear. In this study, we explore the role of circ_0008365 in OA. Methods CHON-001 cells were treated with interleukin-1β (IL-1β) to construct an in vitro OA cell model. The levels of circ_0008365, SRY-related high mobility group-box gene9 (SOX9) mRNA, and microRNA-338-3p (miR-338-3p) were detected by quantitative real-time polymerase chain reaction (qRT-PCR) assay. Western blot (WB) assay was used to measure protein levels. Cell Counting Kit-8 (CCK-8) assay, 5-ethynyl-2′-deoxyuridine (EDU) assay, and flow cytometry analysis were used to detect cell viability, proliferation, and apoptosis, respectively. Dual-luciferase reporter assay, RNA pull-down assay, and RNA immunoprecipitation (RIP) assays were used to confirm the interaction between miR-338-3p with circ_0008365 or SOX9. Results Circ_0008365 expression was reduced in OA tissues and IL-1β-induced CHON-001 cells. Functionally, circ_0008365 inhibited viability, proliferation, and ECM degradation and promoted apoptosis of IL-1β-induced CHON-001 cells. Mechanistically, circ_0008365 acted as a sponge of miR-338-3p to regulate SOX9 expression, thus exerting its functions in IL-1β-induced CHON-001 cells. Moreover, exosomal circ_0008365 had great value in diagnosing OA. Conclusion Circ_0008365 alleviates IL-1β-induced CHON-001 cell damage through the miR-338-3p/SOX9 axis, which suggested that circ_0008365 might be a new therapeutic target for OA.